2015
DOI: 10.3389/fncom.2015.00061
|View full text |Cite
|
Sign up to set email alerts
|

A stimulus-dependent spike threshold is an optimal neural coder

Abstract: A neural code based on sequences of spikes can consume a significant portion of the brain's energy budget. Thus, energy considerations would dictate that spiking activity be kept as low as possible. However, a high spike-rate improves the coding and representation of signals in spike trains, particularly in sensory systems. These are competing demands, and selective pressure has presumably worked to optimize coding by apportioning a minimum number of spikes so as to maximize coding fidelity. The mechanisms by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(47 citation statements)
references
References 50 publications
4
43
0
Order By: Relevance
“…Thus with few exceptions (see below), adaptive threshold models have been qualitative. They demonstrate some features of experimentally observed ISI distributions, and at best correlations between adjacent ISIs In recent years deterministic adaptive threshold models with an exponential kernel have been used to predict spike-times from cortical and peripheral neurons [37,39,54] (see [38] for an early review) and predict peri-stimulus time histograms [39,41] with good accuracy. Capturing spike-times accurately is perhaps the first requirement in our analysis, and this gives confidence that the model may tell us something about ISI correlations.…”
Section: Type III Serial Correlation Coefficientsmentioning
confidence: 73%
See 3 more Smart Citations
“…Thus with few exceptions (see below), adaptive threshold models have been qualitative. They demonstrate some features of experimentally observed ISI distributions, and at best correlations between adjacent ISIs In recent years deterministic adaptive threshold models with an exponential kernel have been used to predict spike-times from cortical and peripheral neurons [37,39,54] (see [38] for an early review) and predict peri-stimulus time histograms [39,41] with good accuracy. Capturing spike-times accurately is perhaps the first requirement in our analysis, and this gives confidence that the model may tell us something about ISI correlations.…”
Section: Type III Serial Correlation Coefficientsmentioning
confidence: 73%
“…outward potassium currents, including voltage gated potassium currents and calcium-dependent or AHP currents (e.g., [5,30,[32][33][34][35][36]). An adaptive threshold model is known to accurately predict spike-times in neurons ranging from cortical [37][38][39] to peripheral [39]. Further, we recently showed that a spike-timing code based on an adaptive threshold is an optimal neural code which minimizes coding error (estimation error) for a fixed long-term spike-rate (energy consumption) [39][40][41].…”
Section: Several Reports Have Suggested That An Adaptive Threshold Mamentioning
confidence: 99%
See 2 more Smart Citations
“…Our adaptation and onset models are similar or equivalent to membrane potential and synapse dynamics that are found throughout the nervous system (see Methods and Appendix). Adaptation allows neurons to minimize energy costs while encoding persistent stimuli (Jones et al, 2015) and to increase their sensitivity to new stimuli (Fairhall et al, 2001). At the population level, excitatory-inhibitory networks are often found in other sensory modalities, such as in orientation tuning in vision (Ben-Yishai et al, 1995) or in the detection of touch in the field of somatosensation (Mountcastle, 1959).…”
Section: Discussionmentioning
confidence: 99%